Fenologia, produção e superação da dormência do mirtilo em ambiente protegido - Coletti, Roberto (2009)
Blueberry is a plant that requires the cold of fall/winter. The lack of fulfilling these needs can cause deficient and non-uniform budding and blooming, with consequences on yield. In two experiments the objective of this research was to study the phenology and yield of blueberry cultivars, with and without the breaking of artificial dormancy. The studies were conducted in an agricultural greenhouse placed in the northeast-southeast direction (200m2), with drip irrigation. Implantation of thecropwasin December 2005, at a spacing of 0.7 m x 2.0 m. In the first experiment, without treatments for breaking dormancy, phenology and yield were evaluated in the third cycle of the cultivars Georgiagem, Clímax, Aliceblue, Elliotte, Brigitta Blue and Bluecrop. In the second experiment, the cultivars Georgiagem, Clímax and Aliceblue were submitted to treatments with hydrogen cyanamide (HC) at the doses of 0.52% and 1.04% (1% and 2% of the commercial product Dormex®), with the addition of 0.5% of mineral oil (MO), comparing them with a control without application. The plants were not submitted to lopping of branches before the application. Without artificial breaking of dormancy, the cultivars Georgiagem, Aliceblue and Clímax present earlier blooming, in August, while Elliotte, Brigitta Blue and Bluecrop are later, in the middle of October. The beginning of harvest is earlierin the cultivars Georgiagem, Clímax and Aliceblue (second half of November), and later in the other cultivars (end of December/beginning of January), scaling production. Yield is greater in the cultivars Bluecrop and Elliotte, and lower in Georgiagem. Chemical induction of breaking dormancy at the end of July does not affect the percentage of bud break and blooming, but in the cultivars Georgiagem and Clímax causes earlier bud break. The treatment of breaking dormancy standardizes flowering, reducing its duration to around 30 to 35 days in the cultivars Georgiagem and Aliceblue, and around 6 to 10 days in Clímax. The use of HC at the concentrations of 0.52% and 1.04%, in combination with 0.5% of MO, reduces yield, possibly through causing phytotoxic effects on the flowering buds